2014
DOI: 10.1177/1687814020935331
|View full text |Cite
|
Sign up to set email alerts
|

A new multiaxial fatigue life prediction model considering additional hardening effect

Abstract: The established linear fatigue life prediction model based on the Miner rule has been widely applied to fatigue life prediction under constant amplitude uniaxial and multiaxial loading. Considering the physical significance of crack formation and propagation, a multiaxial equivalent linear fatigue life prediction model is put forward based on Miner rule and critical plane method under constant amplitude loading. The essence of this approach is that the equivalent strain, which consists of the shear strain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It can be observed that ∆ε np increases by increasing β to a value of about 80 • , and then decreases with the exception of loading condition No. 13.…”
Section: Criterion Drawbacksmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that ∆ε np increases by increasing β to a value of about 80 • , and then decreases with the exception of loading condition No. 13.…”
Section: Criterion Drawbacksmentioning
confidence: 99%
“…By implementing the tensile Manson-Coffin equation (see Equation (10)) in the fatigue limit condition represented by Equation (13), that is:…”
Section: Damage Parameter Under Proportional Loadingmentioning
confidence: 99%
See 1 more Smart Citation